Multiband Pattern Synthesis of Time-Modulated Conformal Array with Quadratic Convex Optimization Algorithm - Dong, Xiao; Li, Hailin; Wang, Ke; Zhang, Yanwei; Chu, Yongyan (International journal of RF and microwave computer-aided engineering, 2023)
Aiming at the multiband pattern synthesis problem of time-modulated conformal array antenna, a quadratic convex optimization algorithm is proposed for sum and difference beamforming with low sidelobe levels. This articles method synthesizes a difference beam with a low sidelobe level by generating nulls at the center frequency band and optimizing the switch-on duration time of array elements. And the sum beamforming and sidelobe suppression of the first-order sideband are realized by optimizing the switch-on instant time of the array elements. The proposed algorithm has excellent properties of sidelobe suppression and angular sweep. The simulation results of circular and satellite array antenna verify the effectiveness of the algorithm.